Relativistic quark model for describing the bound state properties of a tetraquark meson - Zhaugasheva С.А.; Saidullaeva Г.Г.; Baktygereeva Е.С. (Recent Contributions to Physics, 2025)
In modern nuclear and high-energy physics, the explanation of the internal structure of hadrons is one of the most important problems. One of the exotic hadrons studied in recent years is the X(3872) meson. This particle was first discovered in the Belle experiment in 2003 and still has no clear idea of its nature. One of the most interesting issues for today’s day-X(3872) - this is the problem of interpreting the Meson. It is considered as a molecule associated with unsaturated energy, as a tetraquark, which is associated with the existence of dikvarkov.The experimental and theoretical studies of the X(3872) meson property, which were obtained in the collaborations of Belle, BaBar, CDF and DØ, are briefly described. In our work, we considered the X(3872) meson as a tetraquark and calculated the decay width It has been established that the X(3872) meson is not a diquark molecule, but is precisely a tetraquark structure. Covariant Lagrangians describing the effective interaction of hadrons with their constituent quarks are discussed. A definition of the connectivity condition is given, which is an effective tool for describing bound states in the framework of quantum field theory. The concept of infrared confinement is introduced, which ensures the absence of any threshold singularities corresponding to the birth of quarks in the amplitudes of physical processes. The widths of the decays are calculated: X→J/ψ+2π(3π) going through the intermediate states ρ(ω). For reasonable values of the parameter that characterizes the size of the X(3872)meson, agreement with experimental data was found. This analysis was carried out within the framework of the relativistic model of constituent quarks, taking into account their confinement. The results of the study can become the basis for a deeper understanding of the internal structure of meson X(3872) and future research on the description of multi-quark systems.